The expectations of others - Ezequiel García-Lembergman; Ina Hajdini; John Leer; Mathieu Pedemonte; Raphael Schoenle (Inter-American Development Bank (IDB), 2024)
Using a novel dataset that integrates inflation expectations with information on social network connections, we show that inflation expectations within one's social network have a positive, causal relationship with individual inflation expectations. This relationship is stronger for groups that share common demographic characteristics such as gender, income, or political affiliation and when salient information disseminates through the network. In a monetary union New-Keynesian model, socially determined inflation expectations induce imperfect risk-sharing and can affect the inflation and real output propagation of local and aggregate shocks. To reduce welfare losses due to socially determined expectations, monetary policy should optimally put more weight on the inflation rate of socially more connected regions.
Keywords: E31; E71; C83; 330; Inflation expectations; Social network; Monetary union